Literatura polska i „strażnicy milczenia”. Mechanizmy cenzury w PRL kontra praktyki obronne - Dabert, Dobrochna (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The article attempts to synthesise the issue of institutional censorship mechanisms in the Polish People’s Republic which affected the literary communities and literature itself. It also analyses the techniques that writers and literary critics used in order to limit the damage done by the censors. The extended preventive and repressive censorship spawned the phenomenon of self-censorship whose scale has yet to be fully assessed. The detailed research into literary censorship so far allows one to claim that in the discussed period, it is exactly this phenomenon that caused most damage, limiting the freedom of creative expression on a scale that is difficult to estimate.